C-MAC© videolaryngoscopy: The anaesthetic assistant's view. Issue 4 (April 2018) - Jones, Lydia; Mulcahy, Kathleen; Fox, Jeremy; Cook, Tim M; Kelly, Fiona E
Although videolaryngoscopy plays a major role in the 2015 Difficult Airway Society guidelines, the impact on anaesthetic assistant working practices and training has not previously been reported. We surveyed anaesthetic assistants in our hospital to document their experience with using the C-MAC © videolaryngoscope (48 practitioners, 100% response rate). Improvements in the following were reported: patient safety 100%; ability to see whether laryngoscopy is difficult 98%; ability to anticipate the 'next step' 98%; team-working and human factors 96%; ability to call a senior anaesthetist more quickly 94%; assessment or adjustment of cricoid force application 92%, understanding of laryngeal anatomy 92%; training in intubation 98%; training in cricoid force application 87%. Concerns were primarily about local issues such as decontamination and blade availability. Ninety percent reported that the clinical benefit outweighed any additional workload. In conclusion, the C-MAC © videolaryngoscope is judged by anaesthetic assistants to confer numerous advantages for their working practice and training.